A study on communication method between two humans during cooperative task - Shahriman, Abu Bakar; Ryojun, Ikeura; Ahmad Faizal, Salleh; Takemi, Yuno (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.